Outcome prediction criteria for multiple trauma patients with combined cranio-thoracic injuries - Stupnytskyi, Myroslav; Biletskyi, Oleksii (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Blunt chest trauma and traumatic brain injury are considered two of the most significant injury entities with a high potential for complications. In the early post-traumatic period, trauma care frequently encounters limitations in diagnostic capabilities within trauma centers. The objective of this study was to develop simple signs to predict outcomes at three time points during the early post-traumatic period for patients with multiple blunt trauma with combined cranio-tho racic injuries. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This retrospective cohort study was conducted on 51 polytraumatized male patients. Examinations of the patients were performed on the 1st–2nd, 3rd–4th,and 5th–6th day after trauma. Mortality was set as the primary outcome. Re ceiver operating characteristic curve analysis was used to investigate the predictive capacity of the estimated markers for each time period. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The most significant differences between survivors and non-survivors on the 1st to 2nd day after trauma were ob served in terms of SpO2 /FiO2 index, hemoglobin and red blood cell count. On the 3rd–4th day – SpO2 /FiO2 index. The oxygen content, SpO2 /FiO2 index and hemoglobin exhibited the greatest disparity between patients groups on the 5th–6th day. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. A set of criteria can be employed to monitor the clinical course of multiple trauma patients with combined cra nio-thoracic injuries. The predictive value of special markers varies depending on the time period. Each of the investigated time periods is characterized by its own specific predictive signs. The predictive capacity of the estimated markers varies depending on the time period under consideration. It is not an accurate approach to employ the same predictive markers throughout the entire posttraumatic period.